Myth, magic, and farce : four multicultural plays - Houston, Sterling, 1945- (Book collections on Project MUSE., 2005)
These plays represent Sterling Houston's themes and styles. High Yellow Rose deflates the Alamo myth by casting the heroes as women. Isis in Nubia sets the Isis/Osiris myth in West Africa. Black Lily and White Lily is a domestic drama exploring racial tensions. Miranda Rites enacts Martha Mitchell's last days in hospital.